Public interests (Al-Masalih Al-Mursalah) in Islamic jurisprudence: an analysis of the concepts in the Shafi'i school - Wan Azhar Wan Ahmad (International Islamic University Malaysia (IIUM), 2003)
tr,1/ws.c.1